Recovery-focused mental health care planning and co-ordination in acute inpatient mental health settings: a cross national comparative mixed methods study - Michael Coffey; Ben Hannigan; Sally Barlow; Martin Cartwright; Rachel Cohen; Alison Faulkner; Aled Jones; Alan Simpson (BMC Psychiatry, 2019)
Abstract Background Involving mental health service users in planning and reviewing their care can help personalised care focused on recovery, with the aim of developing goals specific to the individual and designed to maximise achievements and social integration. We aimed to ascertain the views of service users, carers and staff in acute inpatient wards on factors that facilitated or acted as barriers to collaborative, recovery-focused care. Methods A cross-national comparative mixed-methods study involving 19 mental health wards in six service provider sites in England and Wales. This included a survey using established standardised measures of service users (n = 301) and staff (n = 290) and embedded case studies involving interviews with staff, service users and carers (n = 76). Quantitative and qualitative data were analysed within and across sites using descriptive and inferential statistics, and framework method. Results For service users, when recovery-oriented focus was high, the quality of care was rated highly, as was the quality of therapeutic relationships. For staff, there was a moderate correlation between recovery orientation and quality of therapeutic relationships, with considerable variability. Staff members rated the quality of therapeutic relationships higher than service users did. Staff accounts of routine collaboration contrasted with a more mixed picture in service user accounts. Definitions and understandings of recovery varied, as did views of hospital care in promoting recovery. Managing risk was a central issue for staff, and service users were aware of measures taken to keep them safe, although their involvement in discussions was less apparent. Conclusions There is positive practice within acute inpatient wards, with evidence of commitment to safe, respectful, compassionate care. Recovery ideas were evident but there remained ambivalence on their relevance to inpatient care. Service users were aware of efforts taken to keep them safe, but despite measures described by staff, they did not feel routinely involved in care planning or risk management decisions. Research on increasing therapeutic contact time, shared decision making in risk assessment and using recovery focused tools could further promote personalised and recovery-focused care planning. This paper arises from a larger study published by National Institute for Health Research (Simpson A, et al, Health Serv Deliv Res 5(26), 2017).